Immunomodulation of Human Mesenchymal Stem/Stromal Cells in Intervertebral Disc Degeneration: Insights From a Proinflammatory/Degenerative Ex Vivo Model. Issue 12 (15th June 2018) - Teixeira, Graciosa Q.; Pereira, Catarina Leite; Ferreira, Joana R.; Maia, André F.; Gomez-Lazaro, Maria; Barbosa, Mário A.; Neidlinger-Wilke, Cornelia; Goncalves, Raquel M.
Abstract : Study Design: Ex vivo experimental study. Objective: To investigate the effect of proinflammatory/degenerative intervertebral disc (IVD) microenvironment on the regenerative and immunomodulatory behavior of mesenchymal stem/stromal cells (MSCs), using an ex vivo model from bovine origin. Summary of Background Data: Low back pain is a cause of disability worldwide, most frequently associated with IVD degeneration and inflammation, and characterized by increased levels of inflammatory mediators, often disregarded. MSC-based therapies to low back pain have been advocated, but the involvement of inflammation in IVD remodeling mechanism, promoted by MSCs has not yet been explored. Methods: Bovine IVD organ cultures of nucleus pulposus punches were stimulated with needle puncture and culture medium supplementation with 10 ng/mL of interleukin (IL)-1β, to induce a proinflammatory/degenerative environment, as previously established. Human bone marrow–derived MSCs were cultured on top of transwells, placed above nucleus pulposus punches, for up to 16 days. MSCs were analyzed by screening cell viability/apoptosis, metabolic activity, migration, and inflammatory cytokines production in response to the proinflammatory environment. IVD extracellular matrix (ECM) remodeling, gene expression profile of IVD cells, and inflammatory cytokine profile in the presence of MSCs in basal versus proinflammatory conditions were also evaluated. Results: Proinflammatory/degenerative IVD conditions did not affect MSCs viability, but promoted cell migration, while increasing IL-6, IL-8, monocyte chemoattractant protein-1, and prostaglandin E2 and reducing transforming growth factor-β1 production by MSCs. MSCs did not stimulate ECM production (namely type II collagen or aggrecan) in neither basal nor inflammatory conditions, instead MSCs downregulated bovine proinflammatory IL-6, IL-8, and TNF-α gene expression levels in IL-1β-stimulated IVDs. Conclusion: The present study provides evidence for an immunomodulatory paracrine effect of MSCs in degenerated IVD without an apparent effect in ECM remodeling, and suggest an MSCs mechanism-of-action dependent on a cytokine feedback loop. Level of Evidence: 5 Abstract : Supplemental Digital Content is available in the text